ANALYSIS OF STUDENT ERROR BASED ON NEWMAN'S PROCEDURE IN SOLVING HOTS TYPES REVIEWING FROM COGNITIVE STYLE FI and FD - Kadek Adi Wibawa; Ni Kadek Indri Wira Pratiwi; I Made Wena (Prima: Jurnal Pendidikan Matematika, 2023)
The purpose of this study was to determine the types of errors and the causes of errors made by students in solving HOTS type questions for SPLTV material based on Newman's procedure in terms of the cognitive style of class X students of Senior High School number six Denpasar. The method of this research is a qualitative method. The data was collected by means of the HOTS test, GEFT, interviews, and documentation. The subjects of this study were students of class X IPA 1 SMA Negeri 6 Denpasar which were then grouped based on cognitive styles, namely Field Independent (FI) and Field Dependent (FD) students and the number of errors in each cognitive style in answering HOTS questions was categorized into 3, namely errors quite complex, complex, and very complex. The average percentage of FI student errors is 38.88%. The average percentage of FD students' errors is 55.55%. The errors of students with cognitive style FD are more than students with cognitive style FI. The causes of errors in the subject of FI are (1) less calm in working on questions, (2) lack of knowledge of the steps that must be taken to solve problems, (3) lack of time in solving problems. completion process, and (4) no re-checking of written answers. The causes of FD student errors are (1) incomplete in reading the questions, (2) in a hurry to finish quickly, (3) not knowing what is known in the questions implicitly, and (4) not checking again.